Pelatihan Pembuatan Tote Bag Ramah Lingkungan dengan Penerapan Teknologi Ecoprint Teknik Pounding pada Ibu-ibu PKK RT 03 Dukuh Sanggrahan, Tirtoadi, Mlati, Sleman - Yuliana Rizka Handayani; Daereo Dzakwan Putra Widana; Rachael Arnesta Torey; Anya Yuniza D; Annisa Hafshah A; Unan Yusmaniar Oktiawati (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Ecoprint is a technique to create patterns on fabric or other materials using natural substances as dyes. This ecoprint technique employs natural materials such as leaves and flowers. Nowadays, ecoprint can be applied to various items, including tote bags. The production of ecoprinted tote bags represents a new step in promoting environmentally friendly products. During the Student Community Service Learning (Kuliah Kerja Nyata or KKN) of the second period of academic year 2023 at Gadjah Mada University, in Unit YO057 located in the Mlati region, specifically in the Tirtoadi Village, the theme of "Poverty Alleviation” waschosen. One of the initiated program was the "Development of Business Culture Through the Dissemination of Ecoprint Making to member of housewives society in the Sanggrahan Hamlet, Tirtoadi Village, as an Effort to Develop Micro, Small, and Medium Enterprises (UMKM)." Community engagement activities related to this theme were carried out through the dissemination of ecoprint making, resulting in the production of environmentally friendly tote bags. The collaborative creation of ecoprinted tote bags with the member of housewives society of RT 03 Dukuh Sanggrahan aims to develop their talents and enable them to establish micro home-based businesses. The pounding technique is an easily accessible ecoprinting method that can be applied during activities with the members of housewives society. The ecoprint creation process produces finished products in the form of tote bags with ecoprint motifs, utilizing natural materials such as leaves found around RT 03 Dukuh Sanggrahan. The member of housewives society of RT 03 Dukuh Sanggrahan demonstrated their ability to produce environmentally friendly tote bags using the ecoprint pounding technique. With the implementation of this activity, it is hoped that the role of women in Dukuh Sanggrahan will expand, providing opportunities for home-based businesses and contributing to positive sustainability effects in the future.